2013
DOI: 10.1016/j.molcel.2013.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Nap1 Shields Histone Surfaces Used in a Nucleosome and Can Put H2A-H2B in an Unconventional Tetrameric Form

Abstract: Summary The histone H2A-H2B heterodimer is an integral component of the nucleosome. The cellular localization and deposition of H2A-H2B into chromatin is regulated by numerous factors including histone chaperones such as Nucleosome Assembly Protein 1 (Nap1). We use hydrogen-deuterium exchange coupled to mass spectrometry to characterize H2A-H2B and Nap1. Unexpectedly, we find that at low ionic strength the α-helices in H2A-H2B are frequently sampling partially disordered conformations, and that binding to Nap1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
92
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 49 publications
(83 reference statements)
9
92
3
4
Order By: Relevance
“…However, in the presence of H2A–H2B, self‐assembly was more pronounced when these flexible tails were absent. In all experiments, and in agreement with our structure, we found that a single H2A–H2B dimer binds to a yNap1 dimer and we could not confirm the stoichiometry proposed by D'Arcy et al (2013). These data confirm that a single yNap1 dimer binds to a single H2A–H2B heterodimer and that this complex self‐assembles into higher‐order oligomers.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…However, in the presence of H2A–H2B, self‐assembly was more pronounced when these flexible tails were absent. In all experiments, and in agreement with our structure, we found that a single H2A–H2B dimer binds to a yNap1 dimer and we could not confirm the stoichiometry proposed by D'Arcy et al (2013). These data confirm that a single yNap1 dimer binds to a single H2A–H2B heterodimer and that this complex self‐assembles into higher‐order oligomers.…”
Section: Resultssupporting
confidence: 51%
“…Previous low‐resolution hydrogen–deuterium exchange experiments suggested that a yNap1 dimer accommodates two copies of H2A–H2B in a tetrameric conformation (D'Arcy et al , 2013). Instead, we found that only a single H2A–H2B heterodimer can be accommodated in the binding pocket of a Nap1 dimer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Так, в статье [1] приведен обзор раз-личных функций белка Nap1, преимущественно его уча-стие в сборке и разборке нуклеосомы, взаимодействие белка Nap1 с различными факторами ремоделирования хроматина, приведена информация о различных участках связывания белка Nap1 с другими белками. В [2] авторы использовали водно-дейтериевый обмен в сочетании с масс-спектрометрией для нахождения участков связыва-ния димера (H2A−H2B) с белком Nap1. В результате выполненной работы авторы установили, что при низкой ионной силе гистоны в димере (H2A−H2B) могут находиться в неупорядоченной конформации, однако связывание димера (H2A−H2B) с Nap1 уменьшает эту структурную неупорядоченность.…”
Section: Introductionunclassified